Gut microbiome of women diagnosed with breast cancer within Pahang, Malaysia - Abd Khalid, Nurul Syazwani; Mahno, Noor Ezmas; Dean Tay, Darren; Ahmad, Hajar Fauzan; Kasian, Junaini; Othman, Ahmad Faidzal; Alias, Norsyuhada; Termizi, Sahrol Azmi; Che Mohamed, Siti Kamariah (British Society of Gastroenterology and BMJ, 2022)
Background Breast cancer is an ongoing issue that is plaguing many young women especially within the regions of Asia. Many factors have been studied thoroughly and have been ruled out over the years. Nevertheless, emergent studies towards the gut microbiome suggest its potential as another cause or treatment to the current predicament. This study aims to elucidate the role of the microbiome in relation to breast cancer by comparing the observed gut flora within healthy individuals to those afflicted with breast cancer in Pahang, Malaysia.